2000
DOI: 10.1046/j.1526-4610.2000.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast in the Prophylaxis of Migraine: A Potential Role for Leukotriene Modifiers

Abstract: We conclude, given the limitations of an open-label study design and the small sample size, that montelukast shows potential as an effective, well-tolerated prophylactic agent in migraine. Double-blinded, placebo-controlled studies are warranted. In addition, the leukotrienes, as suggested previously in the literature, may play a role in the pathogenesis of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
2
31
2
2
Order By: Relevance
“…LTC 4 , however, does not affect the mechanosensitivity of airway afferents (Riccio et al, 1996). In our current study, we found that LTC 4 did not affect meningeal nociceptors even when applied at the highest dose and for up to 1 h. Although there is evidence to suggest that leukotriene receptor modifiers, such as montelukast, which blocks signal transduction through the leukotriene receptor CysLT1 (Funk, 2005), can serve as prophylactic migraine drugs (Sheftell et al, 2000), our results suggest that if LTC 4 or its metabolites play a role in migraine precipitation, their action may not be mediated by promoting the activation or sensitization of meningeal nociceptors.…”
Section: Discussioncontrasting
confidence: 53%
“…LTC 4 , however, does not affect the mechanosensitivity of airway afferents (Riccio et al, 1996). In our current study, we found that LTC 4 did not affect meningeal nociceptors even when applied at the highest dose and for up to 1 h. Although there is evidence to suggest that leukotriene receptor modifiers, such as montelukast, which blocks signal transduction through the leukotriene receptor CysLT1 (Funk, 2005), can serve as prophylactic migraine drugs (Sheftell et al, 2000), our results suggest that if LTC 4 or its metabolites play a role in migraine precipitation, their action may not be mediated by promoting the activation or sensitization of meningeal nociceptors.…”
Section: Discussioncontrasting
confidence: 53%
“…These studies have shown the following: 1) that plasma histamine levels are elevated during migraine attacks in a subpopulation of migraineurs [20]; 2) the ability of histamine infusion to promote a migraine-like headache in most patients [21]; and 3) that antihistaminergic drugs can serve as potent prophylactic agents in migraine [22][23][24]. Recent studies also have implicated other proinfl ammatory MC-derived molecules in migraine pathophysiology, including leukotrienes [25], tumor necrosis factor (TNF)-α, interleukin (IL)-6 [6], and endothelin-1 [26]. Finally, a role for MC in migraine has been suggested based on epidemiological studies showing a signifi cantly higher prevalence of migraine in patients affl icted with other MC-related disorders such as asthma, eczema, rhinitis, and interstitial cystitis [27].…”
Section: Evidence For Mast Cell Involvement In Migrainementioning
confidence: 99%
“…While the role of mast cells in pathogenesis of asthma is well established, there is growing evidence that mast cells contribute to migraine genesis as well by secretion of vasoactive, pro-inflammatory, and neurosensitizing mediators following trigeminal activation [95]. However after encouraging open label trials montelukast [91], an agent blocking the action of leukotriene D4, which is released from mast cells and mediates inflammation, failed to prove efficacy in migraine prophylaxis [16].…”
Section: Migraine Asthma and Allergiesmentioning
confidence: 99%